Affordability after subsidy shift from parallel exchange rate to insurance: a retrospective cross sectional study - Hadi Abbasian; Saman Zartab (Tehran University of Medical Sciences, 2023)
Background: Due to the imposition of an embargo, Iran adopted a policy of a parallel exchange rate. After three years, the advantages and disadvantages of this policy were revealed empirically. Therefore, the government decided to shift the subsidy to insurance instead of the exchange rate. However, as a result of this plan, the price of medicine rose sharply, and affordability decreased for some sections of society who were not covered by any insurance. This study evaluated the impact of this policy on the affordability of essential medicines listed by the WHO. Methods: The impact of this plan on the affordability of essential medicines was evaluated using the WHO recommended method. A cross-sectional study was conducted to measure the affordability of the national essential medicines list before and after the implementation of the subsidy shift from exchange rate to insurance. Results: Despite the benefits of this plan, 17 items in the essential medicine list became unaffordable. The affordability of essential medicines decreased, particularly for uninsured individuals. Conclusion: More efforts should be made to cover uninsured people to preserve their access to essential medicines. Although the shift from parallel exchange rate to insurance had several benefits, such as reducing corruption and reverse smuggling, it also decreased the affordability of essential medicines, particularly for uninsured individuals. Therefore, policymakers should consider implementing measures to ensure that essential medicines remain affordable and accessible to all members of society.